Does Subtelomeric Position of COMMD5 Influence Cancer Progression? - Campion, Carole G.; Verissimo, Thomas; Cossette, Suzanne; Tremblay, Johanne (Frontiers in Oncology, 2021)
The COMMD proteins are a family of ten pleiotropic factors which are widely conserved throughout evolution and are involved in the regulation of many cellular and physiological processes. COMMD proteins are mainly expressed in adult tissue and their downregulation has been correlated with tumor progression and poor prognosis in cancer. Among this family, COMMD5 emerged as a versatile modulator of tumor progression. Its expression can range from being downregulated to highly up regulated in a variety of cancer types. Accordingly, two opposing functions could be proposed for COMMD5 in cancer. Our studies supported a role for COMMD5 in the establishment and maintenance of the epithelial cell phenotype, suggesting a tumor suppressor function. However, genetic alterations leading to amplification of COMMD5 proteins have also been observed in various types of cancer, suggesting an oncogenic function. Interestingly, COMMD5 is the only member of this family that is located at the extreme end of chromosome 8, near its telomere. Here, we review some data concerning expression and role of COMMD5 and propose a novel rationale for the potential link between the subtelomeric position of COMMD5 on chromosome 8 and its contrasting functions in cancer.